Reperfusion Therapy Frequency and Outcomes in Mild Ischemic Stroke in the United States. Issue 11 (November 2020) - Saber, Hamidreza; Khatibi, Kasra; Szeder, Viktor; Tateshima, Satoshi; Colby, Geoffrey P.; Nour, May; Jahan, Reza; Duckwiler, Gary; Liebeskind, David S.; Saver, Jeffrey L.
Abstract : Background and Purpose: More than half of patients with acute ischemic stroke have minor neurological deficits; however, the frequency and outcomes of reperfusion therapy in regular practice has not been well-delineated. Methods: Analysis of US National Inpatient Sample of hospitalizations with acute ischemic stroke and mild deficits (National Institutes of Health Stroke Scale [NIHSS] score 0–5) from October 1, 2016, to December 31, 2017. Patient- and hospital-level characteristics associated with use and outcome of reperfusion therapies were analyzed. Primary outcomes included excellent discharge disposition (discharge to home without assistance); poor discharge disposition (discharge to facility or death); in-hospital mortality; and radiological intracranial hemorrhage. Results: Among 179 710 acute ischemic stroke admissions with recorded NIHSS during the 15-month study period, 103 765 (57.7%) had mild strokes (47.3% women; median age, 69 [interquartile range, 59–79] years; median NIHSS score of 2 [interquartile range, 1–4]). Considering reperfusion therapies among strokes with documented NIHSS, mild deficit hospitalizations accounted for 40.0% of IVT and 10.7% of mechanical thrombectomy procedures. Characteristics associated with IVT and with mechanical thrombectomy utilization were younger age, absence of diabetes, higher NIHSS score, larger/teaching hospital status, and Western US region. Excellent discharge outcome occurred in 48.2% of all mild strokes, and in multivariable analysis, was associated with younger age, male sex, White race, lower NIHSS score, absence of diabetes, heart failure, and kidney disease, and IVT use. IVT was associated with increased likelihood of excellent outcome (odds ratio, 1.90 [95% CI, 1.71–2.13], P <0.001) despite an increased risk of intracranial hemorrhage (odds ratio, 1.41 [95% CI, 1.09–1.83], P <0.001). Conclusions: In national US practice, more than one-half of acute ischemic stroke hospitalizations had mild deficits, accounting for 4 of every 10 IVT and 1 of every 10 mechanical thrombectomy treatments, and IVT use was associated with increased discharge to home despite increased intracranial hemorrhage.